Pengembangan Aplikasi Biomotor Paddletest Berbasis Smartphone - Januar Inggar Yadi; Edwin Wahyu Dirgantoro; Lazuardy Akbar Fauzan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to produce a design for the development of a smartphone-based biomotor paddletest application. An application is a program that is ready to be used to carry out a specific function for application service users as well as other applications that can be utilized by a targeted user group. An application also refers to problem-solving using a data processing technique that is generally oriented toward a desired or expected competency. The method used was Research and Development with the ADDIE design (Analysis, Design, Development, Implementation, and Evaluation). Data analysis employed descriptive statistics with percentage-based results. The results of the study indicate that there is a need for an application that supports coaches’ performance. It is expected that the application will be attractive and beneficial for swimming coaches. In conclusion, the implementation of the smartphone-based biomotor paddletest application aims to improve physical condition abilities, introduce innovation to reduce boredom during training sessions, and enhance coaches’ knowledge in delivering physical conditioning materials to their athletes. Keywords: Application, Biomotor, Paddletest, Smartphone